2011
DOI: 10.4261/1305-3825.dir.4260-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of bleeding events after robotic pancreaticobiliary surgery

Abstract: CONCLUSION Endovascular therapy provides a minimally invasive, safe, and effective method for managing hemorrhagic events after complicated pancreaticobiliary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Where possible, bleeding vessels should be embolised 13. Recent studies have shown embolisation to be successful in the treatment of ruptured aneuryms secondary to pancreatitis14 and in post-operative bleeding events 15. Only tertiary centres provide this service; fast diagnosis and transfer from district general hospitals are therefore indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, bleeding vessels should be embolised 13. Recent studies have shown embolisation to be successful in the treatment of ruptured aneuryms secondary to pancreatitis14 and in post-operative bleeding events 15. Only tertiary centres provide this service; fast diagnosis and transfer from district general hospitals are therefore indicated.…”
Section: Discussionmentioning
confidence: 99%